Analisis Kerusakan Dump Truck HD785-7 Menggunakan Metode Pareto, FMEA dan SCAT - Darsini, Darsini; Susanto, Galih (Indonesian Society of Applied Science, 2024)
PT Saptaindra Sejati (SIS) is a company currently known as a company engaged in mining Services. Companies are required to meet predetermined production targets to meet production targets must be supported by good production unit performance. This research discusses the damage to the Dump Truck HD785-7 production unit which causes a decrease in performance so that the company's productivity is not optimal. To reduce or prevent the failure of the HD785-7 Dump Truck, it is necessary to implement an improvement in good operation and maintenance. The methods used to overcome the poor performance of production units are Pareto method, Failure Mode and Effect Analyze (FMEA) and Systematic Cause Analysis Technique (SCAT). With the Pareto method to create a bar graph based on the number of events. The FMEA method of failure that occurs can be identified to prioritize. The SCAT method is to be able to analyze the system failure of several sub-systems, the levels below and to see the failure of components. From the results of data processing, it is known that there are 3 defects that have the greatest influence on the performance of the low power 03 damage unit with RPN 360, damage to work lights with RPN 216 and engine damage cannot be started with RPN 189.